Metabolic Fingerprinting for Identifying the Mode of Action of the Fungicide SYP-14288 on Rhizoctonia solani - Liang, Li; Cheng, Xingkai; Dai, Tan; Wang, Zhiwen; Li, Jin; Li, Xueming; Lei, Bin; Liu, Pengfei; Hao, Jianjun; Liu, Xili (Frontiers in Microbiology, 2020)
The fungicide SYP-14288 has high efficiency, low toxicity and broad spectrum in inhibiting both fungi and oomycetes, but its mode of action (MoA) remains unclear on inhibiting fungi. In this study, metabolomic and respiratory activities of Rhizoctonia solani were analyzed for determining the MoA of SYP-14288. R. solani wild-type strains and SYP-14288-resistant mutants were incubated on potato dextrose agar plates amended with either SYP-14288 or one of select fungicides acting on fungal respiration, including complex Ⅰ, Ⅱ, and Ⅲ inhibitors, uncouplers and ATP synthase inhibitors. Mycelial growth was measured under fungicide treatments. ATP content was determined using an ATP assay kit, membrane potential of mitochondria was detected with the JC-1 kit, and respiratory rate was calculated based on the measurement of oxygen consumption of R. solani. A model of metabolic fingerprinting cluster was established to group oxidative inhibitors and phosphorylation inhibitors. All the results together displayed a clear discrimination of phosphorylation inhibitors as ATP synthase inhibitors or uncouplers from oxidative inhibitors. SYP-14288 was placed into phosphorylation inhibitor group by metabolic fingerprinting. It significantly reduced ATP content and membrane potential of mitochondria while increasing respiratory rate in R. solani. Therefore, the MoA of SYP-14288 on R. solani was confirmed to involve phosphorylation inhibition and possibly uncoupling activity.